SYNTHESIS, CHARACTERIZATION AND PERFORMANCE EVALUATION OF AMINE MIXED MATRIX MEMBRANES FOR CO2/CH4 SEPARATION - RIZWAN NASIR, . (2016)
For efficient separation of gases, high performance gas separating membranes is desired. Mixed matrix membranes (MMMs) are emerging membranes but these membranes experienced agglomeration of fillers and weak adhesion of fillers and polymer matrix. The main objective of this study is to synthesize enhanced MMMs comprising of polyethersulfone (PES), carbon molecular sieve (CMS 10-30 wt. %) and di-ethanolamine (DEA 5-15 wt. %) which is having high carbon dioxide (C02) affinity for improvement of membrane morphology and performance. The membranes morphology, physirnrVipmiral thermal and mRr.hnnir.nl properties wore analysed systematically.